The challenges of change processes for nurse leaders-a qualitative study of long‐term leaders' experiences over 25 years - Marianne Frilund; Lisbeth Fagerstrøm; Frøydis Vasset (Wiley, 2023)
Abstract Aim This study aimed to map what experiences nurse leaders have encountered concerning the change work that political decisions and reforms have created within the healthcare sector in the last 25 years. Design A qualitative design with a narrative approach was used. Methods A qualitative study involved individual interviews of eight nurse managers from Norway and Finland with more than 25 years of experience working in specialist and primary healthcare fields. Results Two main categories were observed: experiences of organizational challenges and experiences of personnel‐administrative challenges. The first main category included two subcategories: A: historical experience with culture and challenges in health services and B: historical experience with mergers and using welfare technology in health services. The second category included the following subcategories: A: historical experience of job satisfaction for leaders and employees and B experiences with interprofessional collaboration in health services.